2018
DOI: 10.5935/abc.20180039
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Aerobic Exercise Training Associated to Non-Invasive Ventilation in Patients with Acute Heart Failure

Abstract: BackgroundExercise training (ET) improves functional capacity in chronic heart failure (HF). However, ET effects in acute HF are unknown.ObjectiveTo investigate the effects of ET alone or combined with noninvasive ventilation (NIV) compared with standard medical treatment during hospitalization in acute HF patients.MethodsTwenty-nine patients (systolic HF) were randomized into three groups: control (Control - only standard medical treatment); ET with placebo NIV (ET+Sham) and ET+NIV (NIV with 14 and 8 cmH2O of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(32 citation statements)
references
References 34 publications
1
26
0
3
Order By: Relevance
“…The study evaluated patients hospitalized for acute decompensated HF, and found functional benefits and reduced length of stay. 201 Nevertheless, additional studies are needed to confirm these initial results before a stronger recommendation can be issued.…”
Section: Heart Failurementioning
confidence: 99%
See 1 more Smart Citation
“…The study evaluated patients hospitalized for acute decompensated HF, and found functional benefits and reduced length of stay. 201 Nevertheless, additional studies are needed to confirm these initial results before a stronger recommendation can be issued.…”
Section: Heart Failurementioning
confidence: 99%
“…Low-intensity aerobic exercises with noninvasive ventilation during the hospital phase of HF 201 IIb B/C HF: heart failure; LVEF: left ventricular ejection fraction.…”
Section: Recommendation Level Of Evidencementioning
confidence: 99%
“…The literature review identified a total of 14 studies from a total of 6751 articles, of which eight were RCTs, [23][24][25][28][29][30][31][32] three retrospective studies 20,33,34 and one each of a propensity-matched trial, 35 single group pre-/post-study, 36 and case series. 37 Studies varied with time of initiation of CR (ie, during hospitalization, at discharge, or within 6 wk of discharge).…”
Section: Resultsmentioning
confidence: 99%
“…Traditionally, this group of patients was often excluded from CR due to the presence of dyspnea at rest and the fear of acute exacerbation in symptoms and vitals after exercise. However, in recent years, as research on CR in ADHF has gradually been intensified, patients in NYHA class IV have also started to be included in some studies ( 27 ). In this study, although patients in NYHA class IV had significantly more amounts of pulmonary water than patients in class II/III at baseline, they did not show an increase after the test.…”
Section: Discussionmentioning
confidence: 99%